Physiological Status of Adult Bali Cattle in Rearing Under the Shade of Coconut Trees - Endrawati, Eny; Utami, Sri (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to evaluate environmental conditions and heat tolerance coefficient (HTC) values in rearing Bali cattle at the farmer level. This research will begin with conducting a site survey to see the condition of livestock in the field. Then proceed with measuring the environmental and physiological conditions of livestock. The measured data includes rectal temperature and respiratory frequency, HTC values, ambient temperature and humidity and Humidity Temperature Index (HTI) values. Data was taken twice a day for two weeks. Data were collected in the morning and evening after feeding. Rectal temperature measurements, respiration frequency taken at the same time. The results showed that the rectal temperature of Bali cattle was in normal conditions while the respiratory frequency was above normal, the temperature and humidity were high, causing the productivity of cattle to be not optimal.